2016
DOI: 10.1016/j.jclinepi.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Mendelian randomization: how to interpret evidence of shared genetic predictors

Abstract: ObjectiveMendelian randomization is a popular technique for assessing and estimating the causal effects of risk factors. If genetic variants which are instrumental variables for a risk factor are shown to be additionally associated with a disease outcome, then the risk factor is a cause of the disease. However, in many cases, the instrumental variable assumptions are not plausible, or are in doubt. In this paper, we provide a theoretical classification of scenarios in which a causal conclusion is justified or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 48 publications
2
79
0
Order By: Relevance
“…Burgess and colleagues suggested that variants with known biology are better for use in MR studies [49]. The underlying biology of some of the SNPs (those selected from functional literature) included in our analysis is known, and linked to changes in alcohol metabolism, and as such, would be better for use in a PGRS MR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess and colleagues suggested that variants with known biology are better for use in MR studies [49]. The underlying biology of some of the SNPs (those selected from functional literature) included in our analysis is known, and linked to changes in alcohol metabolism, and as such, would be better for use in a PGRS MR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A full discussion on adjustment of covariates in IV analysis is beyond the scope of this manuscript; further information is available elsewhere [23]. Although these assumptions are restrictive, we note that even if these parametric assumptions are not satisfied, a Mendelian randomization investigation can still be interpreted as a test of the causal null hypothesis, even if the magnitude of the causal effect estimate does not have an interpretation [24,25]. Hence, while these assumptions are necessary to ensure the same causal effect parameter is identified by all IVs, and so that the methods provide consistent estimates of a causal parameter (even in a two-sample setting), causal inferences from the methods (that is, rejection or otherwise of the null hypothesis of no causal effect) are valid under much weaker assumptions.…”
Section: Summarized Data Methods (Correlated Ivs)mentioning
confidence: 99%
“…In the context of Mendelian randomization, this means that not only should the magnitude of a causal estimate not be overinterpreted [10,36], but even the direction of the causal estimate may be a false guide as to whether the exposure should be increased or decreased unless further assumptions are made.…”
mentioning
confidence: 99%